Performance analysis of diesel engine heat pump incorporated with heat recovery. (5th September 2016) - Shah, N.N.; Huang, M.J.; Hewitt, N.J.
Highlights: Diesel engine heat pump with heat recovery. Water-to-water source heat pump based on R134a. Possibility for different flow temperature for heat distribution system. Possible retrofit application in off-gas or weak electricity network area. Potential to diversify use of fossil fuel, primary energy and CO2 emission savings. Abstract: This paper presents experimental study of diesel engine heat pump (DEHP) system to find potential as retrofit technology in off-gas or weak electricity network area to replace existing gas/oil/electric heating system in domestic sector. Test set-up of diesel engine driven water-to-water heat pump system was built which included heat recovery arrangement from the engine coolant & exhaust gas. The system was designed to meet typical house heating demand in Northern Ireland. Performance of DEHP was evaluated to meet house-heating demand at different flow temperature (35, 45, 55 & 65 °C), a typical requirement of underfloor space heating, medium/high temperature radiators and domestic hot water. The performance was evaluated against four-evaporator water inlet temperature (0, 5, 10 & 15 °C) and at three different engine speed 1600, 2000 & 2400 rpm. Experiment results were analysed in terms of heating/cooling capacity, heat recovery, total heat output, primary energy ratio (PER), isentropic efficiency, etc. Test results showed that DEHP is able to meet house-heating demand with help of heat recovery with reduced system size. Heat recovery contributed in a range of 22–39% in total heat output. It is possible to achieve high flow temperature in a range of 74 °C with help of heat recovery. Overall system PER varied in a range of 0.93–1.33. Speed increment and flow temperature has significant impact on heat recovery, total heat output and PER. A case scenario with different flow temperature to match house-heating demand has been presented to show working potential with different heat distribution system. In addition, DEHP shows good potential to save primary energy consumption and CO2 emissions, a helpful technology to achieve national emission reduction target.